Role of Baicalin and Liver X Receptor Alpha in the Formation of Cholesterol Gallstones in Mice - Geng Chen; Shuodong Wu (Gastroenterology Research and Practice)
This study was aimed at investigating the effect of baicalin on experimental cholesterol gallstones in mice. The mouse gallstone model was induced by feeding with a lithogenic diet, and cholesterol stones were found in the gallbladder. The lithogenic diet caused elevation of triglycerides, cholesterol, and low-density lipoprotein concentrations and descent of high-density lipoprotein concentration in serum. Hyperplasia and inflammatory infiltration were observed in the gallbladder wall of lithogenic diet-fed mice. We also found the increase of cholesterol content and the decrease of bile acid in bile. Real-time PCR and western blot results demonstrated that the expression levels of two enzymes (cholesterol 7α-hydroxylase (CYP7a1) and sterol 12α-hydroxylase (CYP8b1)) to catalyze the synthesis of bile acid from cholesterol were decreased and that two cholesterol transporters (ATP-binding cassette transporter G5/G8 (ABCG5/8)) were increased in the liver of lithogenic diet-fed mice. The lithogenic diet also led to enhanced activity of alanine aminotransferase and aspartate aminotransferase in serum; increased concentrations of tumor necrosis factor-α, interleukin- (IL-) 1β, IL-6, and malondialdehyde; and decreased superoxide dismutase activity in the liver, suggesting inflammatory and oxidative stress. In addition, liver X receptor alpha (LXRα) was increased in the liver. After gavage of baicalin, the lithogenic diet-induced gallstones, hyperlipidemia, gallbladder hyperplasia, inflammation, and oxidative stress in liver and cholesterol metabolism disorders were all alleviated to some degree. The expression of LXRα in the liver was inhibited by baicalin. In addition, the LXRα agonist T0901317 aggravated lithogenic diet-induced harmful symptoms in mice, including the increase of gallstone formation, hyperlipidemia, hepatic injury, inflammation, and oxidative stress. In conclusion, we demonstrated that baicalin played a protective role in a lithogenic diet-induced gallstone mouse model, which may be mediated by inhibition of LXRα activity. These findings may provide novel insights for prevention and therapy of gallstones in the clinic.